2021
DOI: 10.1002/app.51444
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mechanical, thermal, electrical andEMIshielding properties of graphite/carbon fiber reinforced polypropylene composites prepared via a twin screw extruder

Abstract: The present research focuses on the preparation of an efficient material that acts as a deterrent to electromagnetic pollution. In this study, graphite and carbon fiber (CF) reinforced polypropylene (PP) composites (GCF) are prepared using a melt processing technique via a twin‐screw extruder. The prepared composites were evaluated for mechanical, thermal, DC conductivity, and EMI shielding properties. There is a rise in the tensile strength (4.32%) and thermal stability (6.57%) of composites were recorded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…The artificial electromagnetic radiation produced by various electric appliances has become a real problem in the present world. Depending on the type of device, electromagnetic waves occur in a broad frequency range, from 10 4 to 10 12 Hz. Unfortunately, more and more devices work in the same frequency range, resulting in waves accumulating in the form of so-called electromagnetic pollution or electromagnetic interference (EMI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial electromagnetic radiation produced by various electric appliances has become a real problem in the present world. Depending on the type of device, electromagnetic waves occur in a broad frequency range, from 10 4 to 10 12 Hz. Unfortunately, more and more devices work in the same frequency range, resulting in waves accumulating in the form of so-called electromagnetic pollution or electromagnetic interference (EMI).…”
Section: Introductionmentioning
confidence: 99%
“…), which are mixed with the polymers or are applied in the form of coatings [7,10,11]. The other possibility is to use fillers for the polymers in the form of short fibers such as carbon fibers, metal-coated carbon fibers, or stainless steel fibers [12,13]. However, to obtain high electrical or dielectric properties, they need to be added at high concentrations, which causes limitations in their processing by standard industrial techniques and increases the weight of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer/graphite composites reported so far, contained a significantly smaller amount of the functional phase, typically below 35 vol. % [11][12][13][14][15] and/or a higher fiber diameter, especially 1.75 mm to be used in fused deposition modeling 3D printing [16].…”
Section: Fabrication Of Continous Fibermentioning
confidence: 99%
“…10,[18][19][20] It has been observed that high carbon filler loading is required to achieve the desired shielding effectiveness (SE) of the shielding material prepared by the melt processing technique. [21][22][23][24] That is why using more than one carbon filler, an attempt can be made to maintain a high filler loading of carbon fillers. Many types of research have been done so far for EMI shielding of carbon fillerbased polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Graphite, carbon fiber and carbon nanotubes are the most commonly used carbon conductive fillers 10,18–20 . It has been observed that high carbon filler loading is required to achieve the desired shielding effectiveness (SE) of the shielding material prepared by the melt processing technique 21–24 . That is why using more than one carbon filler, an attempt can be made to maintain a high filler loading of carbon fillers.…”
Section: Introductionmentioning
confidence: 99%